Peran Patroli Roda Empat Satuan Sabhara dalam Mencegah Tindak Pidana Curanmor di Wilayah Hukum Polresta Cirebon - Sumaryanto, Awal (Advances in Police Science Research Journal, 2019)
This research is motivated by the increase in criminal acts of motor vehichle theft in the Cirebon Police jurisdiction from 2017 to 2019. The four-wheeled patrol of the Sabhara Unit has a role in preventing criminal offenses in the area of ​​Cirebon Police. This research was conducted with the aim of describing and identifying the description of criminal acts of motor vehichle theft, the role of four-wheeled Sabhara patrols in preventing criminal acts of motor vehichle theft, as well as the factors that influence the implementation of Sabhara Unit's four-wheeled patrol. This research was conducted with a qualitative approach to the type of field research. The research location is in the jurisdiction of the Cirebon Police with a focus on the role of four-wheeled patrol by the Sabhara Unit. Data sources are primary and secondary with data collection techniques by interviewing, observing, and studying documents. Data validity using triangulation of sources, techniques and time. Data analysis techniques are data reduction, data presentation and conclusion drawing. The results of research on the problems analyzed using management theory and the theory of the causes of NKK crimes show that the perpetrators have the intention and the community also provides an opportunity for the perpetrators to carry out their actions. The role of the Sabhara Unit's four-wheeled patrol in its implementation is still not in accordance with the specified plan. Inhibiting factors are, lack of personnel, lack of personnel capability, lack of budget provided, as well as lack of awareness of the people of Cirebon Regency on property and security. Based on the results of the study, the authors suggest that cooperation with other Technical Functions such as Community development to conduct counseling to the public so as not to neglect their safety, Intel to search for locations prone to fraud and Criminal Investigation to find out the modus operandi of the perpetrators. Utilization of the number of existing personnel, utilization of the amount of the budget by adhering to the principle of priority, the existence of proposals from the police station that were blown to the HR Karo to do vocational education or development education against patrol members. Giving rewards and punishment to patrol members as well as conducting patrols at vulnerable hours from 00.00 a.m. until dawn to be more maximized.